Coordinating Gene Expression and Axon Assembly to Control Axon Growth: Potential Role of GSK3 Signaling - Zhou, Fengquan (Frontiers in Molecular Neuroscience, 2012)
Axon growth requires coordinated regulation of gene expression in the neuronal soma, anterograde transport of synthesized raw materials along the axon, and assembly of cytoskeleton and membranes in the nerve growth cone. Glycogen synthase kinase 3 (GSK3) signaling has recently been shown to play key roles in regulation of axonal transport and cytoskeletal assembly during axon growth. GSK3 signaling is also known to regulate gene expression via controlling the functions of many transcription factors, suggesting that GSK3 may be an important regulator of gene transcription supporting axon growth. Here we will review signaling pathways that control local axon assembly at the growth cone and gene expression in the soma during developmental or regenerative axon growth and discuss the potential involvement of GSK3 signaling in these processes, with a particular focus on how GSK3 signaling modulates the function of axon growth-associated transcription factors.